Erratum to: Allergen immunotherapy for allergic asthma: protocol for a systematic review. Issue 1 (15th September 2017) - Dhami, Sangeeta; Nurmatov, Ulugbek; Agache, Ioana; Lau, Susanne; Muraro, Antonella; Jutel, Marek; Roberts, Graham; Akdis, Cezmi; Bonini, Matteo; Calderon, Moises; Casale, Thomas; Cavkaytar, Ozlem; et al.
Abstract : Unfortunately this article [1] was published with an error in the Funding section. The BM4SIT project is not acknowledged. This section should be corrected to the below: Funding EAACI and the BM4SIT project (Grant Number 601763) in the European Union's Seventh Framework Programme FP7.